Manufacturing Industry Environment: The Effect of Incentive Structures on Group Performance - Fahmi Rizani; Sondakh Grivaldi Antonius; Sarwani Sarwani (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2018)
In the manufacturing industry environment, assembly lines and teams are applied to several industries such as Ford's automotive industry that implements assembly lines and Volvo which implements teams (Libby and Thorne, 2009). This study aims to examine the effect of incentive structures on group performance in a manufacturing environment. The incentive structures used in this study are individual incentives, group incentives, and mixed incentives, while the manufacturing environment used is the assembly line and team. This research is a laboratory experiment which involved 150 students as the subject sample for the study and it used factorial design 3 x 2 between subjects. The subject sample was assigned to a create building using bricks in accordance with the instructions. The results showed that the incentive structure influenced the group performance on the assembly line and team. It was found that in a team, group incentives motivate group members to interact, share information, and work together to produce more wonderful results, group incentives produce higher group performance than individual and mixed incentives. In regard to assembly lines, individual incentives resulted into higher group performance than group and mixed incentives, since individual incentives tend to motivate individuals to work for better output(s).